2002
DOI: 10.1074/jbc.m109967200
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-directed Cross-linking to Subunit B Suggests That Subunit E Forms Part of the Peripheral Stalk of the Vacuolar H+-ATPase

Abstract: We have employed a combination of site-directed mutagenesis and covalent cross-linking to identify subunits in close proximity to subunit B in the vacuolar H ؉ -ATPase (V-ATPase) complex. Unique cysteine residues were introduced into a Cys-less form of subunit B, and the V-ATPase complex in isolated vacuolar membranes from each mutant strain was reacted with the bifunctional, photoactivable maleimide reagent 4-(N-maleimido)benzophenone. are predicted to reside near the bottom of V 1 , with all four residues pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
94
2

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 74 publications
11
94
2
Order By: Relevance
“…However, recent cross-linking experiments have suggested that the Esubunit occupies a peripheral position (58). Such an exposed position agrees with several regulatory protein-protein interactions described for the E-subunit (59,60).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, recent cross-linking experiments have suggested that the Esubunit occupies a peripheral position (58). Such an exposed position agrees with several regulatory protein-protein interactions described for the E-subunit (59,60).…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, we reasoned that the faint stalk in V-ATPases was probably partly formed by one or two (63) copies of the G-subunit and the E-subunit. The E-subunit was shown to be associated with the G-subunit (62)(63)(64) and is located at the periphery of V 1 (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using yeast two-hybrid assay and co-immunoprecipitation, Landolt-Marticorena et al (10) showed that the a subunit of V-ATPase interacts with the H and A subunits. Arata et al (11) showed that the B and E subunits of V-ATPase are in close proximity to each other by introducing unique cysteine residues into a cysteine-less form of the B subunit of V-ATPase and cross-linking purified vacuolar membranes. Their findings suggest that the E subunit forms part of the peripheral stalk of V-ATPase.…”
Section: Vacuolar Hmentioning
confidence: 99%
“…Subunit E forms an elongated structure sitting in the cavity of the V 1 headpiece and subunit C a spherical structure that provides the connection with the rotor in V 0 (Chaban et al 2002). The assignment of subunit E to the central stalk is a matter of debate (e.g., Yokohama et al 2003;Chaban et al 2004;Arata et al 2002). Building subcomplexes from isolated subunits is likely to be the best way to resolve this issue.…”
Section: Introductionmentioning
confidence: 99%